2020
DOI: 10.1167/iovs.61.5.45
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Tuning in Nucleus Prepositus Hypoglossi of Monkeys With “A” Pattern Exotropia

Abstract: In many individuals with pattern strabismus, the vertical misalignment varies with horizontal eye position. It has been proposed that these cross-axis effects result from abnormal cross-talk between brainstem structures that would normally encode horizontal and vertical eye position and velocity. The nucleus prepositus hypoglossi (NPH) is an ideal structure to test this overarching hypothesis. Neurons in the NPH are believed to mathematically integrate eye velocity signals to generate a tonic signal related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…Additionally, in recent years, we have shown directional abnormalities in both microstimulation and recording studies in several brainstem regions 9 11 , 13 , 49 , 50 and the present results are consistent with these previously published studies. Finally, similar abnormalities are observed in monkeys that did not undergo eye muscle surgery.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, in recent years, we have shown directional abnormalities in both microstimulation and recording studies in several brainstem regions 9 11 , 13 , 49 , 50 and the present results are consistent with these previously published studies. Finally, similar abnormalities are observed in monkeys that did not undergo eye muscle surgery.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, in our previous studies, we have consistently found that the results were very similar between an animal that underwent eye muscle surgery in infancy and those for which strabismus was induced using other procedures (such as wearing prism goggles). 9 , 11 13 , 24 , 49 , 50 …”
Section: Discussionmentioning
confidence: 99%